P452 A nurse-led HIV pre-exposure prophylaxis program at cool aid community health centre for men who have sex with men. (14th July 2019) - Lundgren, Karen
Abstract : Background: Gay, bisexual and MSM continue to comprise the greatest number of new HIV diagnosis in BC (BCCDC, 2016). The complexity of the HIV epidemic among MSM has highlighted the need for broader approaches to HIV prevention. Publicly funded access to PrEP in BC began in 2018. The low barrier MSM STI testing clinic at Cool Aid CHC demonstrates that PrEP can be implemented successfully through a nurse-led program. Methods: Description of model of care/intervention: This novel CHC based Men's STI Testing Clinic is staffed by STI certified practice nurses and run in partnership with AIDS Vancouver Island (AVI). It is advertised through MSM social media sites by the AVI Men's Wellness Coordinator. At the initial visit, clients complete a HIRI-MSM index, a sexual/medical history, required screening and participate in PrEP counseling and education. Physicians review the results and sign the PrEP prescription. Clients without primary care are accepted as patients at the clinic. Results: Effectiveness: Our innovative non-judgemental, nurse-led model has removed barriers to sexual health screening and enrolled 124 MSM in the PrEP program. Initial PrEP screening showed an STI incidence of 19% and a previous syphilis diagnosis in 15% of those screened. After PrEP initiation STI incidence increased by 7%, highlighting the need for continued safer sex education. There have been no HIV infections amongst PrEP recipients. 20% have discontinued PrEP after approval. 56% of those enrolled felt unable to access PrEP through their physician. 44% of PrEP clients are now linked to primary care at Cool Aid CHC, demonstrating that PrEP can be a tool to prevent HIV transmission in MSM, while engaging patients in primary care and regular STI screening. Conclusion: and next steps: This innovative program increased access to PrEP for MSM, increased STI testing/treatment, helped to prevent HIV transmission and linked clients to primary care. Disclosure: No significant relationships.